Kieley, James; Kieley, Mary Theresa. Interview about life in Petty Harbour. - Barrett, Terra (2014)
Interview with James Kieley and Mary Theresa Kieley focuses on growing up in Petty Harbour, children's games and activities, holiday celebrations, community events, musical influence of family, and changes in the community.